Adsorpsi Ion Logam Cd2+ dengan Menggunakan Cangkang Telur Ayam Ras - Nova Fitriani; Desy Kurniawati (Departemen Kimia FMIPA UNP, 2022)
The growing industrial growth has resulted in more and more liquid waste containing heavy metals. Therefore we need a way to reduce these heavy metals. One way is adsorption using eggshells. The purpose of this study was to determine the optimum conditions for the adsorption of Cd2+ metal ions on the effect of variations in pH and stirring speed and to determine the adsorption capacity of eggshells for Cd2+ metal ions. This study used the batch method with variations in pH and stirring speed. The optimum conditions obtained from each variation were at pH 4, and stirring speed at 250 rpm. The adsorption capacity at the variation of pH was 2,3875 mg/g at 42,18% and adsorption capacity at variation in stirring speed was 3,3 mg/g at 24,01%.